Respuesta :
5x(x+3)=x(5x-3)+36
5x^2+15x=5x^2-3x+36
5x^2-5x^2+15x+3x=36
18x=36
x=36/18
x=2
5x^2+15x=5x^2-3x+36
5x^2-5x^2+15x+3x=36
18x=36
x=36/18
x=2
5x^2 + 15x = 5x^2 - 3x + 36
5x^2 - 5x^2 + 15x = 5x^2 - 5x^2 - 3x + 36
15x = -3x + 36
15x + 3x = -3x + 3x + 36
18x = 36
18x ÷ 18 = 36 ÷ 18
x = 2
ANSWER: x = 2
Wait is this math ??? I thiught ut was history
5x^2 - 5x^2 + 15x = 5x^2 - 5x^2 - 3x + 36
15x = -3x + 36
15x + 3x = -3x + 3x + 36
18x = 36
18x ÷ 18 = 36 ÷ 18
x = 2
ANSWER: x = 2
Wait is this math ??? I thiught ut was history